(untitled) (Cardiovascular Journal, 2018)
Objective: The Neurological injury is an important complication after coronary artery bypass surgery (CABG). The incidence of neurocognitive impairment after cardiac surgery varies from 20% to 80%. In this study we tried to analyze this difference of neurologic dysfunction between On-pump CABG and Off-pump CABG (OPCAB). Methods:This is a case control study done in National Institute of Cardiovascular Disease (NICVD), Dhaka during the period of July 2012 to June 2014. Sixty Patients with Ischemic heart disease were the study population. Group- A includes 30 patients underwent on pump CABG, Group-B 30 patients underwent OPCAB. All the patients of both the groups were followed up to 2 month’s postoperatively to find out any neurological and neurocognitive dysfunctionby observing motor function, sensory function,Mini Mantel state (MMS) Examination, orientation, memory, attention and calculation, recall and language test. Results: Neurocognitive dysfunction in the early postoperative period is significantly different among the groups.Neurocognitive dysfunction was more in Group A in comparison to Group B, On 3rd and 8th POD the MINI Mental Scores were found to be significantly lower in On-pump group than those in Off-pump group (22.0 ± 5.28 vs. 25.67 ± 3.34, p = 0.002 and 25.93 ± 3.11 vs. 26.63 ± 2.50, p = 0.023 respectively).This neurocognitive dysfunction gradually improved by the end of two month postoperative period. Only 6.66% patient in Group-A was found neurocognitically dysfunctional and was referred to neurophysician for further treatment. In case of OPCAB Group, no patient suffered fromneuorocognitive dysfunction. Conclusion: This study has convincingly shown cardio-pulmonary bypass (CPB) has had detrimental effect on neurocognitive function in patients who underwent CABG. Cardiovasc. j. 2018; 10(2): 186-193